Metode Kontrasepsi Jangka Panjang Sebagai Perencanaan KB Pascasalin dalam Kelas Ibu Hamil - Mirawati Mirawati; Afiatun Rahmah; Noradina Anggi Agustin; Rahma Alifhia Ariana; Gisna Saufita (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Balikpapan (LPPM UNIBA), 2024)
Knowledge and implementation of the use of contraceptive methods, especially Long-Term Contraceptive Methods (LTCM), is currently still low. In fact, LTCM has several advantages such as a high level of effectiveness, low failure rate, fewer complications or side effects experienced by clients when compared to other contraceptive methods. Pregnant women's classes can be a forum for good socialization of LTCM for planning the use of postpartum contraception. This community service aims to increase public knowledge about LTCM so that it can increase the use of LTCM in the community. The method used in implementing this community service is counseling about LTCM using leaflets and educational videos. The conclusion obtained was that there was an increase in knowledge about LTCM from 75% to 91% and of the 15 participants there were 5 participants who planned to use IUDs and implants as contraception options after postpartum. The hope is that midwives will actively play a role in every counseling exercise for the community so that the community's desire and interest in using long-term contraceptives increases